PENGUJIAN PROGRAM PREDIKSI KECEPATAN POROS ROTOR BERTINGKAT SECARA EKSPERIMENTAL - Sembiring, Alexander; Lubis, Asnawi; Wahyudi, Retno (Politeknik Negeri Sriwijaya, Indonesia, 2024)
In the process of designing a rotor shaft system, there are aspects that need to be considered to produce a well-functioning rotor shaft system when it starts operating. Failures that occur in rotor shaft systems are generally caused by excessive vibrations in the system. This can be avoided by detecting the system's natural frequencies early on, as predicting its natural frequencies can also predict its critical rotational speeds. The critical rotational speeds of the system can be determined by solving its equations of motion using various methods. In this study, the equations of motion of the system were solved using the finite element method, where local matrix equations were determined according to the equations and then global matrix equations were obtained and solved using a direct method, employing the eigenvalues and eigenvectors of the system. A program was designed to predict the critical rotational speeds of the system. The program was implemented using the MATLAB programming language. The results of the program, when compared with laboratory test results, showed a difference of 1.23%-3.69%.